Komunikasi Interpersonal Pimpinan PT. Masaro Jabar Lestari dalam Kolaborasi Pentahelix: Studi Kasus Pengelolaan Sampah di Babakan Ciwaringin, Cirebon - Karimah, Syifa Fauzi; Sofyan, Aning; Kurniadi, Oji (Jurnal Ragam Pengabdian, 2026)
This study analyzes the interpersonal communication of the leader of PT. Masaro Jabar Lestari in developing pentahelix collaboration involving academia, industry, government, community, and media in a waste management project in Babakan Ciwaringin, Cirebon. A qualitative method with a single case-study approach was employed. Data were collected through participatory observation, semi-structured interviews, and documentation, then analyzed using Miles and Huberman's model with source triangulation. The findings show that adaptive interpersonal communication was implemented through four stages—opening, orientation, working, and closing—in both formal and informal contexts. Trust, transparency, deliberation, and a shared vision strengthened collaboration among stakeholders. Positive social perceptions enhanced the leader's credibility, while initial community misunderstandings were addressed through open communication. The study concludes that adaptive, trust-based interpersonal communication is the primary factor supporting successful pentahelix collaboration.